Traffic Light Signal Detector using Average Light Intensity Method - Anindito, Benediktus; Winardi, Slamet; Al-Azam, Moh Noor (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
Electronic Traffic Law Enforcement (ETLE) is a way of using information technology to record a violation of traffic. This ETLE was developed to support security, order, and safety in traffic. Some cities or districts in Indonesia have started to apply this ETLE in several locations, which usually have traffic lights and frequent violations at these locations. In this paper, one of the elements in ETLE is tested, which is a traffic light signal detector, which will be used as a basis for whether a vehicle violates a traffic light or not. This detector uses a CCTV camera mounted on the location. It then analyzed the intensity of several image areas on the traffic lights in red, yellow, and green. From the test results, this method can determine the conditions of the traffic lights with 100% accuracy